2003
DOI: 10.1021/jf026040z
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Comparison of Extraction Efficiency of Pesticides from Surface and Laboratory Water Using Solid-Phase Extraction Disks

Abstract: A continuation of an earlier interlaboratory comparison was conducted (1) to assess solid-phase extraction (SPE) using Empore disks to extract atrazine, bromacil, metolachlor, and chlorpyrifos from various water sources accompanied by different sample shipping and quantitative techniques and (2) to compare quantitative results of individual laboratories with results of one common laboratory. Three replicates of a composite surface water (SW) sample were fortified with the analytes along with three replicates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Both water column and pore water samples were extracted by vacuum filtration over 47 mm Empore C18 and SDB−RPS membranes (3M, Belgium), according to the guidelines of the manufacturer ( ). The Empore C18 membranes consist of bonded silica with a 60 Å pore size to which octadecyl groups are attached, giving the membrane a strongly nonpolar affinity.…”
Section: Methodsmentioning
confidence: 99%
“…Both water column and pore water samples were extracted by vacuum filtration over 47 mm Empore C18 and SDB−RPS membranes (3M, Belgium), according to the guidelines of the manufacturer ( ). The Empore C18 membranes consist of bonded silica with a 60 Å pore size to which octadecyl groups are attached, giving the membrane a strongly nonpolar affinity.…”
Section: Methodsmentioning
confidence: 99%
“…More widely, Knox County grows <270 ha of corn annually (Bowing and Smith 2019), all of which lies downriver from this site. The most recent sampling of the same area of the river showed no atrazine to be present, even when multiple analytical laboratories separately examined the water from this same location (Senseman et al 2003). Based on these factors, these authors strongly assert that the water used in the flooding regimen contained no atrazine.…”
Section: Flooding Plotsmentioning
confidence: 99%
“…Studies were conducted to determine if sample integrity was maintained when pesticides sorbed to the Empore SPE disks were shipped to an analytical laboratory. Results showed that minimal recovery losses were observed during the shipment of disks ( ). Observed losses were pesticide specific when using this two-stage analytical procedure ().…”
Section: Introductionmentioning
confidence: 99%